2001
DOI: 10.1086/319008
|View full text |Cite
|
Sign up to set email alerts
|

On the Hardness‐Intensity Correlation in Gamma‐Ray Burst Pulses

Abstract: We study the hardness-intensity correlation (HIC) in gamma-ray bursts (GRBs). In particular, we analyze the decay phase of pulse structures in their light curves. The study comprises a sample of 82 long pulses selected from 66 long bursts observed by the Burst And Transient Source Experiment (BATSE) on the Compton Gamma-Ray Observatory. We find that at least 57% of these pulses have HICs that can be well described by a power law. A number of the other cases can still be explained with the power law model if va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
115
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 30 publications
16
115
0
Order By: Relevance
“…The measured scatter of the peak -tot relation is 0.17 ± 0.08. This result was reported for the first time by Golenetskii et al [178] and later confirmed by Borgonovo and Ryde [179]; Ghirlanda et al [180]; Guiriec et al [181]; Ghirlanda et al [165].…”
Section: Correlations Between the Energetics And The Peak Energysupporting
confidence: 67%
“…The measured scatter of the peak -tot relation is 0.17 ± 0.08. This result was reported for the first time by Golenetskii et al [178] and later confirmed by Borgonovo and Ryde [179]; Ghirlanda et al [180]; Guiriec et al [181]; Ghirlanda et al [165].…”
Section: Correlations Between the Energetics And The Peak Energysupporting
confidence: 67%
“…2. There may be biases in the results when the analysis is performed on a sample of the brightest events, since there is a tendency for bright GRBs (having higher photon fluxes) to have higher spectral peak energies than faint GRBs (Borgonovo & Ryde 2001;Mallozzi et al 1995). For example, Kaneko et al (2006) burst selection criteria required a peak photon flux on the energy range 50−300 keV greater than 10 photons s −1 cm −2 or a total energy fluence in 20−2000 keV energy range larger than 2.0 × 10 −5 erg cm −2 .…”
Section: Grb Samplesmentioning
confidence: 99%
“…Borgonovo & Ryde 2001;Ryde & Petrosian 2002) that the off-latitude emission that follows an abrupt switch-off of the fireball introduces a spectral-energy dependence, since the observer sees progressively less beamed (and less blue-shifted) emission. However, this could explain only the decaying phase of the pulse.…”
Section: Interpretations Of the Spectral-energy Correlationsmentioning
confidence: 99%